2004
DOI: 10.1007/s00442-004-1601-8
|View full text |Cite
|
Sign up to set email alerts
|

Friend or foe? A behavioral and stable isotopic investigation of an ant–plant symbiosis

Abstract: In ant-plant symbioses, the behavior of ant inhabitants affects the nature of the interaction, ranging from mutualism to parasitism. Mutualistic species confer a benefit to the plant, while parasites reap the benefits of the interaction without reciprocating, potentially resulting in a negative impact on the host plant. Using the ant-plant symbiosis between Cordia alliodora and its ant inhabitants as a model system, I examine the costs and benefits of habitation by the four most common ant inhabitants at La Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 71 publications
2
54
0
Order By: Relevance
“…Some phytoecious ants may consume nothing but extrafloral nectar and/or food bodies (e.g., Pheidole bicornis [Fischer et al 2002] and Pseudomyrmex on Acacia [Heil et al 2004]), even though they have been shown to significantly reduce herbivory on their hosts (Janzen 1967;Letourneau et al 1998), in which case they may reap only the indirect benefits of plant defense. But many, such as A. octoarticulatus, eat at least some of the insects that visit their host plants (e.g., Yu and Pierce 1998;Tillberg 2004). These ants are probably not under strong selection to cheat by not protecting their host plants against herbivores, and they might be expected to be more effective against palatable herbivores than unpalatable ones.…”
Section: Costs Of Plant Defense To a Octoarticulatusmentioning
confidence: 99%
“…Some phytoecious ants may consume nothing but extrafloral nectar and/or food bodies (e.g., Pheidole bicornis [Fischer et al 2002] and Pseudomyrmex on Acacia [Heil et al 2004]), even though they have been shown to significantly reduce herbivory on their hosts (Janzen 1967;Letourneau et al 1998), in which case they may reap only the indirect benefits of plant defense. But many, such as A. octoarticulatus, eat at least some of the insects that visit their host plants (e.g., Yu and Pierce 1998;Tillberg 2004). These ants are probably not under strong selection to cheat by not protecting their host plants against herbivores, and they might be expected to be more effective against palatable herbivores than unpalatable ones.…”
Section: Costs Of Plant Defense To a Octoarticulatusmentioning
confidence: 99%
“…Colonies of A. pittieri usually have one queen and are limited to a single tree (E. G. Pringle, personal observation). A. pittieri ants patrol the leaves and stems of C. alliodora and attack herbivores and other intruders, biting and chasing them off the tree (Tillberg 2004; E. G. Pringle, R. Dirzo, and D. M. Gordon, personal observations). Reports differ on whether Azteca ants significantly reduce herbivory on C. alliodora leaves (Wheeler 1942, Tillberg 2004.…”
Section: Study Systemmentioning
confidence: 99%
“…pittieri ants host both Coccidae (soft scale insects) and Pseudococcidae (mealybugs) inside domatia (Tillberg 2004) and eat their honeydew (E. G. Pringle, personal observation). Individual trees are usually inhabited by several species of coccids, including Cryptostigma reticulolaminae (both sites), Cryptostigma inquilina and Aztecalecanium sp.…”
Section: Study Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…army ants, Hirosawa et al, 2000), and a preponderance of omnivores (Blüthgen et al, 2003;Davidson et al, 2003). Recently, studies have utilized stable isotopes to elucidate the trophic ecology of ants including temporal variation in diet (Fisher et al, 1990;Mooney and Tillberg, in press), the nature of ant-plant symbioses (Treseder et al, 1995;Sagers et al, 2000;Solano and Dejean, 2004;Tillberg, 2004;Trimble and Sagers, 2004), and the community ecology of ants (Blüthgen et al, 2003;Davidson et al, 2003;Tillberg and Breed, 2004).…”
Section: Introductionmentioning
confidence: 99%